PRINSIP TRANSPARANSI DALAM PENGELOLAAN KEUANGAN (STUDI KASUS PADA RSUD KABUPATEN MUNA BARAT) - hadijah, sitti; Nurfaida, Wa Ode Ade; Juliana, Nur; Rohmawati, Wahidah (Jurnal Pijar, 2025)
The increasing public demand for health services provided by hospitals requires hospital management to operate hospitals professionally, including in terms of financial accountability. The implementation of transparency is expected to increase accountability and the level of public trust in hospitals. This study aims to provide an overview of applying the principle of transparency in financial management at the West Muna Regency Hospital. This research uses a qualitative approach with a case study method. The results showed that budget planning was carried out by involving various sections and units in the budget planning process. The process of financial supervision and control involves various parties. Financial audits by external parties such as the Supreme Audit Agency (BPK) are an effort to ensure transparency in financial management. In terms of public accessibility to financial information through financial reports, it is known that there is no online media such as sites that provide financial reports that can be accessed by the public. It is recommended the hospital consider developing and improving policies, especially regarding the publication of financial information, including strategies to publish financial reports through the hospital website to maintain the level of public trust in the hospital.